STUDY ON THE EQUIVALENT PROPERTIES AND ENERGY ABSORPTION PROPERTIES OF A NOVEL MATERIAL WITH NEGATIVE POISSON′S RATIO (MT) - WU XiaoLi; LI ZhaoKai (Jixie qiangdu)
In recent years, negative Poisson′s ratio（NPR） materials have attracted extensive attention from the academic community due to their excellent mechanical properties and huge application potential in traditional industrial fields. The mechanical properties of a new type of material with negative Poisson′s ratio（based on YSH structural cell） under dynamic compression are designed and studied. Through the finite element simulation method, the response difference of different structural parameters（inclined wall angle, width ratio, aspect ratio） to the equivalent elastic mechanical performance parameters of the cell is compared, and the influence of these structural parameters on the energy absorption performance is explored, and the research is further extended to the structure under four common functional gradient arrays. The energy absorption effect of the structure is evaluated by three indexes: energy absorption, energy absorption efficiency and platform stress. The study shows that, inclined wall inclination θ the larger, the better the energy absorption performance of the whole structure; width ratio α it has little influence on the equivalent mechanical properties and energy absorption of the whole structure; aspect ratio β the smaller the value, the more obvious the negative Poisson′s ratio effect of the structure, but on the contrary, the larger the value, the higher the energy absorption efficiency. The results can provide a reference for the function-oriented design of materials with negative Poisson′s ratio.